BEYOND MORTGAGES: ISLAMIC LAW AND THE ETHICS OF CREDIT FINANCING FOR PUBLIC HOUSING - Muhamad Subhi Apriantoro; Eis Rantika Puspa; Dandi Ibtihal Yafi; Deast Amanda Putri; Rozi Irfan Rosyadi (Universitas Muhammadiyah Surakarta, 2023)
Having a home is essential for everyone, and the government created a program called Housing Loan (KPR) to help low-income people own a house. The Sharia State Savings Bank (BTN) is one of the banks that offer this program. This study aims to understand how KPR works at Bank BTN KCPS Pekalongan and how it aligns with Islamic law. This type of research is field research, which outlines and describes phenomena regarding the situation. In this case, the kind of research is qualitative. This research can also be considered sociological research because it is carried out directly in the field, and the data received will be evaluated inductively to make arguments for the KPR transaction system at BTN KCPS Pekalongan with Sharia principles and appropriate legislation. The study found that BTN KCPS Pekalongan uses murabahah and istishna sale and purchase contracts for KPR. Murabahah contracts are commonly used, and Istishna contracts are used for one product called KPR BTN Indent I.B. The study recommends that the bank introduce other Sharia KPR products to the public to increase awareness